(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article discusses the challenges of teaching history in schools and madrasas of Turkestan in the late 19th and early 20th centuries, focusing on the subjects and books taught, particularly the instruction of history. Based on an analysis of sources and literature, the authors suggest that history was not taught as a separate academic subject in traditional religious schools and madrasas. It is noted that history was first studied as a distinct subject in educational institutions established by the Russian colonial authorities in Turkestan. In the national education system, the subject of history was first incorporated into the curricula of new method schools founded by the Jadids. Subject classification codes: include these here if the journal requires them